TRANEXAMIC ACID ON PERIOPERATIVE BLOOD LOSS IN SPINE SURGERY: A PROSPECTIVE OBSERVATIONAL STUDY - NAGHMA, SEHAR E.; RESHMA, THARSIS P.; FARHA, RAJASAB DEEBA; RAKESH, KALAPPA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate the efficacy and safety of tranexamic acid in reducing perioperative blood loss and transfusion requirements in patients undergoing spinal surgery. Methods: This prospective observational study was conducted at MVJ Medical College and Research Hospital from January 2022 to February 2023. Patients undergoing spinal surgery who received perioperative TXA were assessed for intraoperative blood loss, postoperative drain output, transfusion requirements, and adverse events, including thromboembolic complications. Results: The use of TXA was associated with a significant reduction in intraoperative blood loss, postoperative drain output, and transfusion requirements. No increase in thromboembolic or other major adverse events was observed. Conclusion: Perioperative administration of tranexamic acid is a safe and effective blood conservation strategy in spinal surgery, significantly reducing blood loss and transfusion needs without increasing thromboembolic risk.